Biofilms and multidrug resistance: an emerging crisis and the need for multidisciplinary interventions - Yahya, Mohd Fakharul Zaman Raja; Jalil, Mohd Taufiq Mat; Jamil, Norashirene Mohamad; Nor, Nurul Hidayah Mohamad; Alhajj, Nasser; Siburian, Rikson; Majid, Nazia Abdul (Frontiers in Bioengineering and Biotechnology, 2025)
The escalating prevalence of multidrug resistance (MDR) represents not merely a medical challenge, but a systemic shortcoming in our current antimicrobial paradigms. Central to this crisis are biofilms, the structured microbial communities that not only exhibit intrinsic resistance to antibiotics but also facilitate the persistence of dormant cells and the horizontal transfer of resistance genes. While emerging natural and synthetic antimicrobial agents offer potential avenues for intervention, their effectiveness is often limited by issues such as poor bioavailability, toxicity, and production scalability. To overcome these limitations, the field must shift from incremental refinements to transformative strategies. Promising approaches include electrochemical biofilm disruption, phage-antibiotic synergistic therapies, nanoparticle-mediated delivery systems, CRISPR-based genome editing, natural quorum sensing inhibitors, and the application of next-generation probiotics. However, scientific innovation alone is insufficient. A comprehensive response must also encompass policy reform: implementing strict regulations on antibiotic usage in agriculture, incentivizing the development and adoption of rapid diagnostic tools, and adapting clinical trial designs to support the evaluation of combinatorial and multimodal therapies. Addressing biofilm-associated MDR requires a radical, multidisciplinary approach to effectively counter this growing global threat.